Price Discrimination and Fairness Concerns - Florian Englmaier; Linda Gratz; Markus Reisinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
We analyze the profitability of third degree price discrimination under consideration of consumers' fairness concerns within an experiment and explain the results within a theoretical framework. We find that with an increase in the price differential negative reciprocal reactions by disadvantaged consumers become stronger compared to positive reciprocal reactions by advantaged consumers. Consequently, the profit maximizing price differential lies below the one predicted to be optimal by standard theory. Further, profitability increases when consumers who are regarded as poorer are charged lower prices compared to when the wealth of the different consumer groups is unknown.
urn:nbn:de:bvb:19-epub-12735-6
Keywords: D11; D12; E3; 330; price discrimination; reciprocal fairness; inequity aversion; experimental economics; Preisdifferenzierung; Austauschtheorie (Soziologie); Gerechtigkeit; Konsumentenverhalten; Test